2014
DOI: 10.1097/mib.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications and Emergent Readmission in Children and Adults with Inflammatory Bowel Disease Who Undergo Intestinal Resection

Abstract: Readmission and postoperative complications are common after intestinal resection in CD and UC. Clinicians should closely monitor surgical patients who required emergent admission, undergo surgery with stoma formation, or develop in-hospital postoperative complications to anticipate need for readmission or interventions to prevent readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Of the 21 remaining articles, 9 reported on UC only 5,11,12,26-31 , 4 reported on CD only [32][33][34][35] , and 8 reported on both UC and CD. [36][37][38][39][40][41][42][43] Details of the included studies are shown in Table 1 Regardless of the reason for the difference in mortality between emergent and elective surgery, these data highlights the need to reduce the rate of emergent operations for IBD.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the 21 remaining articles, 9 reported on UC only 5,11,12,26-31 , 4 reported on CD only [32][33][34][35] , and 8 reported on both UC and CD. [36][37][38][39][40][41][42][43] Details of the included studies are shown in Table 1 Regardless of the reason for the difference in mortality between emergent and elective surgery, these data highlights the need to reduce the rate of emergent operations for IBD.…”
Section: Resultsmentioning
confidence: 96%
“…This systematic review included population-based studies, however it should be noted that not all population-based studies recruit cases in the same manner; for example, some administrative databases capture all patients in a defined region 36,40 , whereas others use random sampling techniques to identify a population-based subpopulation. 11,29 Differences in defining populationbased studies may account for some of the heterogeneity observed between studies.…”
mentioning
confidence: 99%
“…8 Advanced age has been shown in some studies to be an independent risk factor for complications, increased length Q10 of stay, and increased operating room time in CD patients. [8][9][10][11] The American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) is a large prospective surgical database. It has the capacity to evaluate the occurrence of postoperative complications and define the clinical setting within which they occur.…”
Section: Q7 Q8 Q9mentioning
confidence: 98%
“…58 The existing literature on IBD readmissions after non-surgical hospitalizations in the US includes single center experiences, where generalizability may be limited. However, these studies have suggested that poorly-controlled pain and depression, 9 and lack of compliance with outpatient follow-up 4 were associated with a higher likelihood of readmission.…”
Section: Introductionmentioning
confidence: 99%